Calculation of spare elements in complete sets of the ZIP on the basis of DN-distribution - Strelnikov, V.P.; Shou Weichao (Математичні машини і системи, 2009)
Design procedures of sufficiency of the ZIP, quantities of nonrestorable spare elements on the basis of use as theoretical model of refusals of elements and a product of two-parametrical DN -distribution are presented.